Diabetic Self-Management Education – Effect on Self-Management Care of Type-2 Diabetic Patients - Imelda Rahmayunia Kartika; Aria Wahyuni; Nur Fitra Dewi (Universitas Padjadjaran, 2021)
A common problem of a person with diabetes mellitus was the lack of discipline in implementation of their daily self-care management. Diabetes Self-Management Education (DSME) was a system to help diabetes patients manage their activities to improve their health. DSME is the process which can improve the knowledge, skill, and ability of diabetes self-care. This study aimed to determine the effect of using diabetes self-management education (DSME) intervention and how it affected patients’ self-care management. This research was quasi experiment with one group pretest-posttest among patients with type-2 diabetes. There were 30 participants assigned by using purposive sampling into DSME intervention. Four sessions of DSME were conducted to the participants using illustrative media/fliers. The data were collected by questionnaires of Diabetes Self-Care Management. Then, it was analyzed by using paired t-test. The results showed that self-care management of the respondents before the intervention was 28.8 and it increased to 35.3 after the intervention (mean different=6.5). There were differences in the self-care score before and after the intervention (p=0.001). This study has limited time to do DSME. But, in four sessions, we have tried to explain more about diabetes interactively. Then, better to assess the type-2 diabetes patients with qualitative method or mixed with more participants included for the future researchers. This research was adopting a DSME to found significant improvements in the self-care management in type-2 diabetes mellitus patient. This demonstrates that DSME intervention can be such clinical importance in care of type-2 diabetes mellitus patient.Keywords: Diabetes self-management education, self-care management, type-2 diabetes patients.